Hubungan antara Kecemasan dengan Masa Menopause pada Wanita - Harnani, Kharisma Setya; Indrayanto, Yoseph; Dharmawan, Ruben (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background : Menopause is the transition of the reproductive period to the nonreproductive period which happens in women due to the decreased levels of the esterogen and progesterone hormones. There are several symptoms during the menopause period such as physical symptoms, somatic disorders, sexual disorders, and physical disorders. This research aims to describe the relation between anxiety and menopause in women. Methodology : This research is observational analytic research with cross sectional approach. This research was conducted in Posyandu Lansia Dahlia RW XIX Nusukan, Posyandu Lansia RW XIV Nusukan, and Posyandu Lansia Pucangsawit. The samples of this research are the women who had no menstrual period for 1-2 years, women â¥ 40 years old which are not in menopause period yet (control), women with unpathological menopause, L-MMPI scores with âNOâ answers < 10, and the women who are able to be the respondents to fill in and accept the informed consent. This research employs the purposive random sampling technique in which samples are selected based on the characteristics of the research inclusion and exclusion. The dependent variable in this research is menopause and the independent variable is anxiety. The subject of the research filled (1) the curriculum vitae and informed consent, (2) L-MMPI questionnaire to checked the respondentâs truthfulness in filling the questionnaire, (3) TMAS questionnaire to found out the anxiety scores. The data which were obtainedÂ are 60 respondents, then the data were analyzed using Chi Square (x2) then Coeficient Contingency (C). Result : Based on the data analysis, p = 0.01 was obtained from Î± = 0.05 which means p < 0.05 and the relation is 0.317. Conclusion : Statistically, there is significant relation with weak correlation between anxiety and menopause period in women. Â Keywords : Menopause, AnxietyÂ